Écrire une parole coupée : cosmologies et géomancie dans Volatiles (2006) de Kossi Efoui - Chavelet, Diane (Ponti/Ponts, 2024)
We propose here to approach Kossi Efoui’s short story Volatiles (2006) in its metapoetic, allegorical and philosophical dimensions. One of the greatest singularities of Volatiles is indeed the layout of a poetic process through the reinvestment of the geomancy of the Fa. For Kossi Efoui, this reappropriation must be understood as a transgression of literary codes. How then does Kossi Efoui shift the function of writing from a teleology (the design) to a sketch of possible presents (the drawing) through geomancy? To what myths of speech and writing does this practice refer? To what extent do these mythologies provide a poetic horizon for Afrocontemporary literature? After having quickly resituated and redefined geomancy in West Africa, we will reflect on the cosmopoetic dimension that Kossi Efoui gives it as well as the different cosmologies to which he links it in Volatiles, in order to revisit a philosophical myth of the origins of the world in which the scriptural gesture is born from a cut off speech.